The Relationship between Academic Performance and Environmental Sustainability Consciousness: A Case Study in Higher Education - FUCHS, Kevin (Journal of Environmental Management and Tourism, 2021)
Environmental sustainability is a very articulated and complex concept that is widely discussed in many disciplines and many streams of the literature, wherein tourism is dependent upon the environment for much of its well-being. With that being said, tourism education is at the forefront of impacting environmental sustainability in one way or another by educating tomorrow’s tourism stakeholders. This study presents preliminary findings of a larger study that examines a possible relationship between academic performance and tourism students’ consciousness towards environmental sustainability. The Environmental Sustainability Consciousness Questionnaire (ESCQ) was used to gather quantitative data from a sample of undergraduate students (n=100) through the cluster sampling method. The empirical findings of this study suggest that students in the top as well as bottom percentile ranked by academic performance have generally the highest consciousness toward environmental sustainability. Furthermore, a statistically significant correlation was detected between the academic performance of students and their perceived knowledge with regard to environmental sustainability. The results of the study add to the existing boy of knowledge end reveal that academic performance is not an indicator that better-performing students have a higher consciousness toward environmental sustainability.